2021
DOI: 10.1136/bmj.n1227
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19: How the Brazil variant took hold of South America

Abstract: Brazil has long been a pariah in the pandemic, but the consequences of its failure to control SARS-CoV-2 are manifesting across Latin America, writes Luke Taylor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Death cases in Brazil resulting from the coronavirus are expected to rise based on the analysis of this study. This result supports Taylor [ 53 ] in which this report estimated that almost 400000 Brazilians have died from COVID-19, indicating a 13% of the world's total COVID-19 deaths, which is even more than the country's entire AIDS epidemic.…”
Section: Discussionsupporting
confidence: 85%
“…Death cases in Brazil resulting from the coronavirus are expected to rise based on the analysis of this study. This result supports Taylor [ 53 ] in which this report estimated that almost 400000 Brazilians have died from COVID-19, indicating a 13% of the world's total COVID-19 deaths, which is even more than the country's entire AIDS epidemic.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, this is the first report of an animal case infected by the SARS-CoV-2 variant of concern (VOC) P.1 (Gamma) worldwide. Such a VOC caused a dramatic health crisis in Brazil and other countries of South America [ 13 15 ] due to its high infectivity and immune escape capacity [ 16 ]. We highlight that many infections caused by VOC P.1 were registered in Bahia at the time of the cat infection, which moved the state health department to suspend non-essential trips [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed hematological disturbances related to FeLV infection. In general, such pathological signs are accompanied by immunosuppression [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gamma was first identified in Manaus, Brazil, in November 2020 and is another variant of concern for WHO. At the time of writing it remains the dominant variant in South America 10…”
Section: Gammamentioning
confidence: 99%